2021
DOI: 10.21608/tsnj.2021.210227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Care Intervention and Safe-Swallowing Education on Dysphagia among ICU Patients Post Endotracheal Extubation

Abstract: Background: Post Extubation Dysphagia (PED) can potentially cause life-threatening consequences, early detection of PED is essential to reduce complications. Understanding the treatment modalities of PED is essential to minimize complications and improve quality of treatment. Oral care intervention and safe-swallowing education are valuable to improve and prevent dysphagia in vulnerable patients' post-extubation. The aim of this study is to assess the effect of oral care intervention and safe-swallowing educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition, previous research (29) clarified that there was a statistically significant improvement in the total mean score of oral assessment guide that indicate slight to moderate oral problems post intervention compared to pre intervention. Moreover, another previous research (7) showed that there was a dramatic improvement in oral assessment score in the study group on post intervention. In relation to Bazaz dysphagia scale score regarding severity of dysphagia, the current finding revealed that, more than half of the studied children in the study group were having moderate dysphagia after 7 th days and absence of dysphagia after 14 th days of practicing swallowing exercises.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In addition, previous research (29) clarified that there was a statistically significant improvement in the total mean score of oral assessment guide that indicate slight to moderate oral problems post intervention compared to pre intervention. Moreover, another previous research (7) showed that there was a dramatic improvement in oral assessment score in the study group on post intervention. In relation to Bazaz dysphagia scale score regarding severity of dysphagia, the current finding revealed that, more than half of the studied children in the study group were having moderate dysphagia after 7 th days and absence of dysphagia after 14 th days of practicing swallowing exercises.…”
Section: Discussionmentioning
confidence: 66%
“…(4,5) It includes any incapability or difficulty to efficiently and properly move food and drinks from the mouth to the esophagus. (6) Algendy & Bahgat (7) mentioned that up to 62% of intensive care unit patients experience dysphagia after extubation. This prevalence rate of dysphagia may potentially be higher in children due to anatomical variations in the size and physical relationship of the oral structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst swallowing and oral intervention is one of the effective management as brushing of teeth/massaging of salivary glands would improve oral lubrication and oral sensation by mechanically stimulating oral sensory receptors and increasing salivary flow [19,20]. Oral care intervention also includes a range of motion exercises for the lips, tongue, jaw, and cheeks [21]. Oral motor exercise can alleviate lip weakness, tongue strength, lingual agility, and mouth opening by strengthening lips, tongue, jaw, and cheeks [22,23].…”
Section: Introductionmentioning
confidence: 99%